1998
DOI: 10.1034/j.1600-0420.1998.760219.x
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the "dropped nucleus"

Abstract: ABSTRACT.Purpose: To summarize and analyse the results of our experience in treating patients with a ''dropped nucleus''. Methods: The case records of nineteen patients who underwent surgery for a ''dropped nucleus'' at the Ophthalmology Departments of Sahlgren's University Hospital, Gothenburg, and Ö rebro Medical Centre, Ö rebro, Sweden during 1994 were retrospectively reviewed to determine the mode of treatment used and the results of surgery. The frequency of this complication was also calculated for Swede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
3
10
0
1
Order By: Relevance
“…In our study a statistically significant number of retinal detachments was found in those eyes manipulated by the cataract surgeon (pΩ0.01). This supports the view that the cataract surgeon should not try to retrieve the dislocated lens fragments from the vitreous cavity (Kim et al 1994;Margherio et al 1997;Kapusta et al 1996;Aaberg et al 1997;Stenkula et al 1998).…”
Section: Discussionsupporting
confidence: 73%
“…In our study a statistically significant number of retinal detachments was found in those eyes manipulated by the cataract surgeon (pΩ0.01). This supports the view that the cataract surgeon should not try to retrieve the dislocated lens fragments from the vitreous cavity (Kim et al 1994;Margherio et al 1997;Kapusta et al 1996;Aaberg et al 1997;Stenkula et al 1998).…”
Section: Discussionsupporting
confidence: 73%
“…23 With an incidence of RD between 3% and 18% after removal of a dropped nucleus, careful examination of the peripheral retina is advisable, particularly in the first 2 to 3 months. [24][25][26][27][28][29][30][31][32] The older iris-plane lenses severely limited pupil dilation. [33][34][35][36][37] This limitation does not occur with Artisan lenses, allowing good visualization of the peripheral retina.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis estimating each study’s power for comparing outcomes was updated, and the results (mean =24%, median =14%) again indicated that many studies had low power. Figure 2A shows whether SD-PPV or DEL-PPV seemed better for each outcome, for all articles with these data 2,3,6,7,11,12,14,15,1719,22,2427,2931,34,35,40,4345. These SD-PPV vs DEL-PPV results appear mixed and do not obviously favor either vitrectomy time.…”
Section: Resultsmentioning
confidence: 93%
“…However, the logistics of arranging an SD-PPV can be daunting 16,17. Others feel that SD-PPV is unnecessary, complicates the informed consent process, and may increase the risk of complications 18,19. A survey of cataract surgeons indicated they believed that 58% of patients had retained lens fragments removed immediately,20 far higher than reported by vitreoretinal surgeons, who indicated only 13% (536 of 4,150) of eyes received an SD-PPV 21…”
Section: Introductionmentioning
confidence: 99%